24-epibrassinolide confers tolerance against deep-seeding stress in Zea mays L. coleoptile development by phytohormones signaling transduction and their interaction network. (2nd November 2021) - Zhao, Xiaoqiang; Zhong, Yuan; Shi, Jing; Zhou, Wenqi
ABSTRACT: Coleoptile/mesocotyl elongation influence seedling emergence and establishment, is major causes of maize deep-seeding tolerance (DST). Detailed analyses on molecular basis underlying their elongation mediated by brassinosteroid under deep-seeding stress (DSS) could provide meaningful information for key factors controlling their elongation. Here we monitored transcriptome and phytohormones changes specifically in elongating coleoptile/mesocotyl in response to DSS and 24-epibrassinolide (EBR)-signaling. Phenotypically, contrasting maize evolved variant organs to positively respond to DST, longer coleoptile/mesocoty of K12/W64A was a desirable organ for seedling under DSS. Applied-EBR improved maize DST, and their coleoptiles/mesocotyls were further elongated. 15, 607/20, 491 differentially expressed genes (DEGs) were identified in W64A/K12 coleoptile, KEGG analysis showed plant hormone signal transduction, starch and sucrose metabolism, valine, leucine, and isoleucine degradation were critical processes of coleoptile elongation under DSS and EBR signaling, further highly interconnected network maps including 79/142 DEGs for phytohormones were generated. Consistent with these DEGs expression, interactions, and transport, IAA, GA3, ABA, and Cis-ZT were significantly reduced while EBR, Trans-ZT, JA, and SA were clearly increased in coleoptile under DSS and EBR-signaling. These results enrich our knowledge about the genes and phytohormones regulating coleoptile elongation in maize, and help improve future studies on corresponding genes and develop varieties with DST.